Accelerogram Sintetik Sumber Gempa Subduksi Untuk Wilayah Kota Bengkulu - Delfebriyadi, Delfebriyadi (Universitas Andalas, 2024)
This paper describes the creation of synthetic acceleration time history (accelerogram) based on stochastic method using SMSIM v2.3 program and wave scaling technique for a planned earthquake scenario. General description of magnitude and distance of a planned earthquake scenario is taken from the calculation result of seismic deaggregation using probabilistic analysis for Bengkulu city. This study produces 4 synthetic acceleration time histories in subduction zone based on design criteria of building age of 50 years and probability value of 10% exceeded for Sb class soil site.